2010
DOI: 10.1007/s00246-010-9717-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of Moderate Functional Tricuspid Valve Regurgitation at the Time of Pulmonary Valve Replacement: Is Concomitant Tricuspid Valve Repair Necessary?

Abstract: Congenital heart defects with a component of pulmonary stenosis are often palliated in childhood by disrupting the pulmonary valve. Patients often undergo subsequent pulmonary valve replacement (PVR) to protect the heart from the consequences of pulmonary regurgitation. In the presence of associated moderate functional tricuspid valve (TV) regurgitation, it is unclear what factors contribute to persistent TV regurgitation following PVR. In particular, it is unknown whether PVR alone will reduce the right ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 9 publications
2
29
0
Order By: Relevance
“…Judicious use of tricuspid valve annuloplasty, valve repair, and right atrial reduction plasty is indicated when there is evidence of more than mild valvular incompetence to prevent further deterioration and perhaps the onset of atrial arrhythmia. 130,389,[413][414][415][416][417] Some authors also recommend that prophylactic cryoablation be performed in patients with severe tricuspid valve regurgitation and right atrial enlargement to decrease the risk of late arrhythmia.…”
Section: Tricuspid Valve Regurgitationmentioning
confidence: 99%
“…Judicious use of tricuspid valve annuloplasty, valve repair, and right atrial reduction plasty is indicated when there is evidence of more than mild valvular incompetence to prevent further deterioration and perhaps the onset of atrial arrhythmia. 130,389,[413][414][415][416][417] Some authors also recommend that prophylactic cryoablation be performed in patients with severe tricuspid valve regurgitation and right atrial enlargement to decrease the risk of late arrhythmia.…”
Section: Tricuspid Valve Regurgitationmentioning
confidence: 99%
“…A stated before, closure of the ventricular septal defect may also affect tricuspid valve function but did not appear to be a risk factor for tricuspid valve regurgitation in our initial study [3]. Unfortunately, risk may be incurred by adding concomitant tricuspid annuloplasty to pulmonary valve replacement.…”
Section: Functional Tricuspid Regurgitation In Right-sided Heart Diseasementioning
confidence: 56%
“…Upon reviewing the 1-month postoperative echocardiograms after pulmonary valve replacement, we found that moderate and severe tricuspid valve regurgitation improved to a similar degree regardless of whether a concomitant tricuspid valve annuloplasty was performed [3]. We contended that most of the improvement in tricuspid valve function relates to the volume unloading that occurs with pulmonary valve replacement and that concomitant annuloplasty adds very little.…”
Section: Commentmentioning
confidence: 76%
See 2 more Smart Citations